PSYCHOLOGICAL EFFECTS OF OCCUPATIONAL STRESS ON THE WELL-BEING OF CORRECTIONAL STAFF AND THE NEXUS WITH THE BURNOUT SYNDROMЕ - Yordanov, Ivaylo (E-Journal VFU, 2025)
The article will examine the psychological effects of occupational stress and the specifics of the work environment on the well-being and mental health of frontline prison staff, which professional duties are directed to provision of security and safety in these institutions. The focus will be on the main sources of tension in prisons and the ways in which they are connected with the burnout. The key risk factors affecting the mental health of officers will be drawn, as well as recommendations for prevention of burnout through organizational and individual support.